Evaluation of Changing Education System at Universities in The Pandemic Process Based on The Opinions of Faculty Members and Students - Korkmaz, Selma; Gökbulut, Burak; Yeniasır, Mustafa; Özbent, Ayşenur (International Journal of Emerging Technologies in Learning (iJET), 2021)
Covid-19, which emerged in the Wuhan city of People’s Republic of China and affected the whole world, was first seen in Turkish Republic of Northern Cyprus and Turkey in March 2020. Due to the negative impact created by the mentioned disease, face-to-face education which was traditionally applied in Turkey and Northern Cyprus was ceded and total distance education was adopted rapidly so that education would not be hindered. Although distance education has a long history in the world, the total transformation of the system required a certain ef-fort for both students and teachers to have a command in the process. In the arti-cle, based on the opinions of faculty members and students, the education system that has completely changed in universities with the pandemic process is evaluat-ed. The distance education system, which is thought to have an important place in education after today, has been evaluated especially by pointing out the deficien-cies and making some recommendations to eliminate them. In the research, meas-urement and evaluation came to the fore as one of the most important problems in the distance education system. At this point, it is predicted that a more process-oriented measurement and evaluation process will produce healthier results.